MANAJEMEN STRATEGIK DENGAN PENDEKATAN BALANCED SCORECARD DI IAIN SYEKH NURJATI DALAM UPAYA TRANSFORMASI MENJADI UIN - Kurniawan, Asep; Sumadi, Sumadi (Holistik: Journal for Islamic Social Sciences, 2016)
The transformation of IAIN Sheikh Nurjati to a university is an inevitability. This is due to the tendency of the educational market which increasingly leaves "typical" science of IAIN to the general science. In addition, the dichotomy of science is believed to be continuously maintained, If IAIN Sheikh Nurjati is institute. This situation is responded by IAIN Sheikh Nurjati with establishing the plan and strategic management of the university transformation. But apparently, the plan is not accordance with the implementation of its management. Many things that indicate IAIN Sheikh Nurjati is not ready to become a university. The unreadiness could be more obvious when it is viewed by the Balanced Scorecard approach. For that, this research is conducted to evaluate the, so far, the strategic management with the Balanced Scorecard approach in IAIN Sheikh Nurjati in an effort to transform into a university. The reseach is based on the Kaplan’s and Norton’s theory of Balanced Scorecard. The research approach is qualitative. Data collection techniques are in-depth participatory observation, in-depth interviews, documentation, and questionnaires. Qualitative data validation through credibility, transferability, dependability, and confirmability. Meanwhile, the testing of quantitative data through validity test and reliability test. Technical analysis and interpretation of data, namely data collection, data reduction, data display and data conclusion. The reseach found that (1) the expected transformation of IAIN to UIN is to integrate science and to broaden scope of science, (2) The priority programs to be university in the four perspectives of the balanced scorecard are not fully achieved, (3) IAIN is not ready to transform into a university, and (4) transformation efforts are not fully can run well, because of some inhibiting factors. In conclusion, IAIN Sheikh Nurjati requires a breakthrough program to achieve the transformation. Keywords: Strategic Management, Balanced Scorecard, Transformation